Gaya Kepemimpinan Melayani (Servant leadership) Ketua RT 010, RW 003, Pela Mampang, Mampang Prapatan, Jakarta Selatan - Tri Rumayanto; Siti Nurjannah Sanusi; Sri Sutali Bani (Yayasan Literasi Sains Indonesia, 2025)
In a leadership style, there are various leadership styles that exist today, one of which is the servant leadership style. This style is applied by the Head of RT 010, RW 003, Pela Mampang, South Jakarta as the focus of this study. This has led to the growth of satisfaction and trust of the residents of the area to re-elect him. This article uses the theory of servant leadership style with its 10 characteristics. This article also uses a qualitative research method with data collection techniques from primary sources through interviews and secondary sources from books and journals. This article concludes that Mr. Subhan as the Head of RT 010, RW 003 gained the trust of the residents and was re-elected in the RT election because he applied the servant leadership style. The characteristics include, (1) Listening, (2) Empathy, (3) Improving the Abilities of Oneself & Others, (4) Awareness of Oneself & Others, (5) Persuasion Approach, (6) Conceptualization, (7) Ability to See the Future, (8) Stewardship for Society, (9) Commitment to the Growth of Others, (10) Building Community.